Decomposition of Molecular Motions into Translational, Rotational, and Intramolecular Parts by a Projection Operator Technique (Communications in Computational Physics, 2018)
The motion of the atoms in a molecule may be described as a superpositionof translational motion of the molecular center-of-mass, rotational motion about theprincipal molecular axes, and an intramolecular motion that may be associated withvibrations and librations as well as molecular conformational changes. We have constructedprojection operators that use the atomic coordinates and velocities at any twotimes, t=0 and a later time t, to determine the molecular center-of-mass, rotational, andintramolecular motions in a molecular dynamics simulation. This model-independenttechnique facilitates characterization of the atomic motions within a system of complexmolecules and is important for the interpretation of experiments that rely on time correlationfunctions of atomic and molecular positions and velocities. The applicationof the projection operator technique is illustrated for the inelastic neutron scatteringfunctions and for the translational and rotational velocity autocorrelation functions.